Teachers' discourse in kindergarten: An analysis of teachers' utterances in science lessons - Menti, Alejandra Beatriz (2021)
This paper studies the organization of teachers’ utterances taking into account whether they belong to academic or social discourse, and the pragmatic function that teachers’ utterances play within each discourse modality. The data consist of four class hours of video-recorded material obtained during observations of teaching situations in two five-year-old kindergarten groups. One kindergarten belongs to a rural school and the other one, to an urban school. We used qualitative and quantitative data analysis. The results showed that both teachers generated similar discursive contexts in Science lessons. Teachers used more utterances during the development of academic discourse than during social discourse. Within social discourse, the teachers used most of their utterances to issue directives. Within academic discourse, they used most utterances to request information from kindergartners. In this case, the rural teacher and the urban teacher produced similar percentages of utterances for commenting on and evaluating children's responses. Results suggest that it is important to continue studying the pedagogical implications of teaching practices in Science lessons as well as detecting teachers’ training opportunities in classroom dialogue and practices that promote the development of scientific thinking in kindergarteners.